Влияние геометрии аморфных неоднородностей на фотопроводимость с-SI - Бабыченко, О. Ю.; Пащенко, А. Г. (ХНУРЕ, 2018)
The given work is presented perspective directions of modification the silicon structure for obtaining a higher coefficient of transformation in solar cells. A mathematical model is proposed for estimating the effect of the geometry amorphous heterogeneity’s in crystalline silicon on the photoconductivity.
Keywords: Влияние геометрии аморфных неоднородностей; фотопроводимость с-SI